Pelaksanan Pembelajaran Bahasa Indonesia Masa Pandemi Covid-19 di SMA Negeri 11 Pekanbaru - Herawati, Delvina; Supriyadi (UIR PRESS, 2021)
Learning in the Covid-19 Pandemic Period at SMA Negeri 11 Pekanbaru. Undergraduate Program. Riau Islamic University. This research is entitled